Riencourt-lès-Bapaume (Pas-de-Calais) Un gisement du Paléolithique moyen - Tuffreau, Alain (Documents d'archéologie française, 1993)
Construction of the northern TGV line resulted in the rescue excavation of Riencourt-lès-Bapaume. For the first time, it was possible in excavate a Middle Palaeolithic open air site on an area of 10,000 m2. The preliminary contributions brought together in this volume represent analysis completed on short notice using samples drawn from abundant lithic material (approximately 86,000 pieces). The archaeological levels dispersed in the lœssic sequence of the first part of the last glacial, have yielded lithic artifacts which can be assigned to many industries which illustrate the complexity of the Middle Paleolithic. The lithic assemblage of level CA demonstrates the presence of the production of Levallois flakes and another for the production of blades. The functional analysis have shown that both flake and blade reduction technologies are associated with the specific tool functions.